SAT0205 Failure of the Switch from the Intravenous to the Subcutaneous Formulation of Abatacept due to a Disease Reactivation: Our Experience. (9th June 2015) - Reggia, R.; Cavazzana, I.; Tincani, A.; Franceschini, F.
Abstract : Background: Abatacept is a selective T cell costimulation modulator indicated for moderately to severely active Rheumatoid Arthritis (RA). Since August 2013 the new subcutaneous (sc) formulation is available in Italy. Itconsists in a fixed dose of 125 mg of the drug, administered once weekly. Objectives: To retrospectively analyze the clinical response of a cohort of patients (pts) with RA treated with monthly iv infusion who converted to the sc formulation. Methods: We included 49 pts with RA, converted from iv to sc Abatacept from October 2013 to April 2014. We divided them into two groups, depending on their need to switch back to the iv administration for the appearance of a disease flare, defined as a numeric increase in DAS28.The main clinical and serological features of the two groups have been compared using the Chi-square, T-test or the Mann-Whitney test. Results: Fifteen pts (30.6%) returned to the iv administration due to a disease flare (mean DAS28: 4.8 vs 2.1, p<0.001), after a mean of 15 injections (range 4-48): in these pts it has been observed a significant increase of the CRP values (mean: 0.29 vs 0.86 mg/dl, p=0.004) and of the number of painful (mean:0.6 vs 4.9, p<0.001) and swollen joints (mean 0.5 vs 4.2, p<0.001). The remaining 34 pts (69.4%) continued with the sc formulation. The compared parameters between the two groups are summarized in Table 1 . In pts with arthritis flare, disease activity decreased again (mean DAS28: 4.16 vs 2.43, p<0.001) after returning to the iv infusion (mean: 45 days), with a significant decrease in the CRP values (mean 0.9 vs 0.4 mg/dl, p=0.04) and in the number of painful (mean: 4.9 vs 1.7, p=0.003) and swollen joints (mean: 4.2 vs 1.2, p=0.003). Twelve months after the switch, we evaluated the persistence in treatment of the original cohort: 94% (32 over 34) of pts who maintained the sc formulation of Abatacept were still treated with the drug (1 withdrawn for sustained remission and 1 for recurrent infections) while only 67% (10 over 15) of those who had returned to iv administration had maintained Abatacept therapy because 5 of them experienced a disease reactivation and had been swapped to other biologics (p=0.036). Conclusions: Although the safety profile of the sc Abatacept seems to confirm the previously obtained data with the iv use of the drug, a high rate of our patients complained a reduced efficacy, also confirmed by the subanalysis of the objective components of the DAS28 index (CRP values and joints involvement). However this study was retrospective and there were no informations on compliance to the sc formulation in pts who flared. We have failed to identify clear risk factors that may help toward the selection of pts to which propose the formulation switch, however, if an arthritic flare occurs, the return to the iv administration seems to ensure a good control of the disease again. Nevertheless, the switch failure seems to predict a reduced persistence of abatacept efficacy during time. References: Rakieh C, Conaghan PG. Comparative clinical utility of once-weekly subcutaneous abatacept in the management of rheumatoid arthritis. Ther Clin Risk Manag. 2014;10:313-20. Wells AF, Jodat N, Schiff M. A critical evaluation of the role of subcutaneous abatacept in the treatment of rheumatoid arthritis: patient considerations. Biologics. 2014;8:41-55.Review. Disclosure of Interest: None declared